Seeing and sensing single G protein-coupled receptors by atomic force microscopy - Sapra, K Tanuj (Curr Opin Cell Biol, 2019)
G protein-coupled receptors (GPCRs) relay extracellular information across cell membranes through a continuum of conformations that are not always captured in structures. Hence, complementary approaches are required to quantify the physical and chemical properties of the dynamic conformations linking to GPCR function. Atomic force microscopy (AFM)-based high-resolution imaging and force spectroscopy are unique methods to scrutinize GPCRs and to sense their interactions. Here, we exemplify recent AFM-based applications to directly observe the supramolecular assembly of GPCRs in native membranes, to measure the ligand-binding free-energy landscape, and how interactions modulate the structural properties of GPCRs. Common trends in GPCR function are beginning to emerge. We envision that technical developments in combining AFM with superresolution fluorescence imaging will provide insights into how cellular states modulate GPCRs and vice versa.